THE UTILIZATION OF SPENT MUSHROOM COMPOST APPLIED AT DIFFERENT RATES IN TOMATO( LYCOPERSICON ESCULENTUM MILL.) SEEDLING PRODUCTION - Ünal, Mesude (Emirates Journal of Food and Agriculture, 2015)
The purpose of this research was to utilize spent mushroom compost as a seedling cultivation media in vegetative production and provide an alternative to the peat sources on the edge of extinction. Tomato (Lycopersicon esculentum Mill.) was used as a vegetative production material. In this research, 7 different growing media consisting of 100% peat, %100 spent mushroom compost and a mixture of peat+spent mushroom compost+ perlite at varying rates were prepared. According to the results of the research, the values of hypocotyl lengt,seedling root lengt, shoot wet weight and root wet weight gave the best results the seedlings grown in 100% spent mushroom compost (H7),the length of cotyledon contained 25% spent mushroom compost (H5), the width of cotyledon contained 25% spent mushroom compost (H3).Statistically, there was a difference between the mixtures of different cultivation media and hypocotyl length at a level of p<0.05. The best value of hypocotyl length was obtained as 48.00mm from H7, implementation containing 100% spent mushroom compost. According to H1 media containing 100% peat, seedling root length increased in the media which spent mushroom compost was added into and a difference at a level of p<0.05 occured between them. The addition of spent mushroom compost into the cultivation media can be said to have had positive impact on the quality traits of tomato seedling.